High-yield colloidal synthesis of monometallic Au nanorod–Au nanoparticle dimers and their application in SERS. Issue 20 (21st February 2017) - Chen, Suli; Chen, Lei; Hu, Huicheng; Liu, Qipeng; Xu, Yong; Ji, Fei; Bao, Feng; Fan, Jian; Zhang, Qiao
Abstract : Dimeric nanostructures have attracted much attention owing to their unique structure and excellent physiochemical properties. Abstract : Dimeric nanostructures have attracted much attention owing to their unique structure and excellent physiochemical properties. However, it has been very difficult to make monometallic nanodimers. In this work, we report a simple colloidal approach to synthesize high-yield monometallic Au nanorod–Au nanoparticle dimers by using a negatively charged polyelectrolyte, poly(sodium- p -styrenesulfonate) (PSS), to modify the positively charged Au nanorods. The growth process is studied by systematically tuning the reaction parameters. The as-obtained dimers can serve as a great SERS substrate for the detection of organic molecules because of the existence of "hot-spots". The analytical enhancement factor (AEF) of the as-prepared dimers is up to 10 6, which is two magnitudes higher than that of Au nanorods.